A spring visit to Denmark - Burton, P J K (Wildfowl, 1960)
During the spring of 1959, I spent a short time at the reserve of the Danish Naturfredningsrdet at Tipperne in West Jutland. My main purpose was to make observations on the flocks of Brent Geese which collect there in April and May.